Assessment Of Topographic Variation In UMP Gambang Campus Using Land Survey Approach - Muhammad Syafi, Mohd Basri (2023)
The higher education institution Universiti Malaysia Pahang (UMP) concentrates on engineering studies. As soon as you enter the UMP region, you will see several icon-shaped buildings. Numerous flat sections of varying heights make up the land structure that is readily seen. The objectives of this study are to determine the elevation of the topography variant’s terrain relief at UMP Gambang Campus and to provide the current topography mapping accurately. Because Universiti Malaysia Pahang (UMP) is actively implementing programs in support of the Sustainable Development Goals (SDG), which have become a global agenda in accordance with the 17 goals that must be accomplished by all countries by 2030, the topographic conditions observed there need to be explored.